New Trends in Public Sector Management in Health : Applications in Developed and Developing Countries - Shaw, R. Paul (World Bank, Washington, DC, 2013)
This paper begins with a review of the broad motivations behind the New Public Sector Management (NPSM), including intrinsic differences between public and private organizations that appear to impact on incentives and performance. The experience in selected OECD countries is reviewed where the financing and delivery of health and other social services is heavily socialized with a strong public sector role, taxpayers have expressed dissatisfaction with traditional modes of public sector management, and NPSM reforms have been hotly debated. Part II of the paper then describes the NPSM paradigm in terms of three building blocks that influence the performance of public agencies and the behaviors of employees who work for them. It explains how leverage points within the NPSM paradigm are expected to create incentives for improved performance. It is when all three building blocks of the NPSM paradigm work together that synergies are expected to take place, and that continuous improvements in the performance of public agencies are expected to be generated over time. Part III illustrates five organizational strategies that can be used to introduce NPSM into public agencies in the national health system. Much of Part III refers to developing country applications.